The amount of homework in mathematics and its effect on academic performance - Firosmanashvili, Tamar; Tkebuchava, Mimoza ("Intercultural Dialogues" Transactions, 2023)
Giving students homework in mathematics has both difficulties and benefits. Conducted research and our school practice have clearly revealed that a large volume of assignments has a negative impact on student motivation, interest and academic performance. Therefore, we conducted a study on the small amount of homework and its effectiveness. Our respondents were the VII-X graders of Public School N89 of Tbilisi City. The purpose of the conducted research was to determine the causes of low academic results of students, to implement appropriate interventions and to evaluate the achieved results. We got acquainted with international studies and experiences, which helped us in the selection and planning of interventions. Within the framework of the study, a focused observation was conducted, the purpose of which was to investigate whether the performance of homework had an effect on the academic performance of students. The summative works before the beginning of the research were analyzed, the purpose of which was to determine the academic performance of the students. Parents were also surveyed in order to determine their children's involvement in the educational process. Based on practical research, it was determined that a small volume of assignments had a positive effect on their academic performance, students were relieved of stress caused by many assignments and the subject became more interesting for them. They also have more free time, which they use to revise the previous material, which helps to improve their academic performance. The recommendations offered by us will be useful for other teachers of the general education school. We present to you the recommendations developed on the basis of the research conducted by us, which are useful for other teachers of the general education school.